MARKETING PERFORMANCE ANALYSIS OF BATIK MSMES IN SUMENEP REGENCY - Farah Werdimansyah; Masfufatul Khoiriyah; Janna Aulia Pulung Sari; Ahmad Syauqi (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2026)
This study aims to analyze the influence of entrepreneurial orientation, product innovation, and competitive advantage on the marketing performance of batik MSMEs in Sumenep Regency. This study uses a quantitative approach with an associative research type. The population in this study is all batik MSMEs in Sumenep Regency, totaling 35 business units, with the sampling technique using saturated sampling, so that the entire population is used as a research sample. Data analysis methods used include validity tests, reliability tests, and multiple linear regression analysis with t-tests and F-tests. The results of the study indicate that partially entrepreneurial orientation does not significantly influence marketing performance, with a calculated t value of 1.539 and a significance level of 0.134 (>0.05). Product innovation is proven to have a positive and significant effect on marketing performance with a calculated t value of 2.046 and a significance level of 0.049 (<0.05). Meanwhile, competitive advantage does not significantly influence marketing performance with a calculated t value of 0.790 and a significance level of 0.436 (>0.05). Simultaneously, the three independent variables influence marketing performance with a calculated F value of 4.054 and a significance level of 0.015 (<0.05). The conclusion of this study is that product innovation is more influential in improving the marketing performance of batik MSMEs in Sumenep Regency, while entrepreneurial orientation and competitive advantage have not had a significant impact. Therefore, MSMEs are advised to focus more on developing product innovation and optimizing business strategies to sustainably improve marketing performance.